Endoscopic Surgery of Skull Base Chordomas - Tan, Neil C-W; Naidoo, Yuresh; Oue, Sakiko; Alexander, Hamish; Robinson, Simon; Wickremesekera, Agadha; Floreani, Steve; Vrodos, Nick; Santoreneos, Steve; Ooi, Eng; Mcdonald, Matthew; Wormald, Peter-John (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective To assess our clinical experience in treating midline intracranial pathology using minimally invasive surgical techniques.Design Retrospective chart review of patients undergoing endoscopic endonasal resection of clival chordomas.Setting Two tertiary referral centers in Australia and New Zealand.Main Outcome Measures Patients were assessed by intraoperative findings (macroscopic resection rate, tumor size, and operative complications) and clinical outcomes (residual disease, postoperative complications, recurrence rate, and mortality).Results Fourteen patients underwent endoscopic resection of clival chordomas (seven primary, seven revision) with a mean follow-up of 41.45 months (3 to 104 months). Macroscopic resection rates were 71% and 29%, respectively. Mean operative time was 386 minutes. Overall cerebrospinal fluid (CSF) leak rate was 3/14 (21%) and, using the nasoseptal flap, it was 0/5 (0%). Two patients developed late recurrence; one died of disease and one was treated with intensity modulated radiation therapy. Overall mortality was 2/14 (14%).Conclusion Endoscopic resection of clival chordomas is a safe and viable alternative to the traditional open approach. The nasoseptal flap is an excellent method of obtaining a watertight skull base closure. Furthermore, this series highlighted the fact that the primary attempt at surgery offers the best chance to achieve a total resection.
Keywords: chordoma; endoscopic; endonasal; surgery; minimally invasive; skull base